Meso-level bending/reverse-bending analysis of dry woven fabrics: Observing an irreversible behavior during forming. (15th February 2022) - Sourki, R.; Crawford, B.; Vaziri, R.; Milani, A.S.
Abstract: During the design and simulation of woven fabric structures and forming processes, the loading/unloading regimes are often neglected. The overlooked strain history and associated irreversible behavior may have non-negligible impacts on product performance. In this article, it is first experimentally shown that local bending/reverse-bending can occur during a typical hemispherical forming process, and therefore critical mechanical properties such as the fabric bending rigidity can vary non-linearly during deformation, accompanied by a hysteresis. The magnitude of this variation is a function of multiple parameters such as part geometry, fabric crimp, friction, the twist of fibers, among others. A basic meso-level modeling framework has been adopted here to predict the above cyclic bending response of a typical dry glass/polypropylene plain weave. The predicted irreversibility is validated with experiments, using both single-layer and double-layer fabric layouts of different sizes, as well as single yarns.